1979
DOI: 10.1021/j100482a022
|View full text |Cite
|
Sign up to set email alerts
|

Chemical reactivity of supported gold. A structural study by small-angle x-ray scattering and x-ray absorption spectroscopy

Abstract: Preparations of Au supported on Si02 and A1203 were characterized by small-angle X-ray scattering (SAXS), wide-angle X-ray scattering (WAXS), extended X-ray absorption fine structure spectroscopy (EXAFS), and transmission electron microscopy (TEM). The Lm X-ray absorption coefficient was used in the EXAFS analysis and the radial structure function was calculated. The interatomic distances and coordination numbers of Au preparations were obtained. EXAFS data indicated an interaction between Au and A1203, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

1980
1980
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 14 publications
0
22
0
1
Order By: Relevance
“…ESR is also a power tool to study the metal complexes and the nature of the ligands; there is extensive literature on the ESR spectroscopic properties of complexes of copper(II) with 4N or other ligands. [14] Gold(II) compounds would be paramagnetic with electron configuration 5d 9 as copper(II) compounds, it is possible to infer the existence of this oxidation state from a study of the ESR absorption spectra. Although the divalent state of gold is one of the most interesting oxidation states in transition metal chemistry, only a few paramagnetic Au 2+ complexes have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…ESR is also a power tool to study the metal complexes and the nature of the ligands; there is extensive literature on the ESR spectroscopic properties of complexes of copper(II) with 4N or other ligands. [14] Gold(II) compounds would be paramagnetic with electron configuration 5d 9 as copper(II) compounds, it is possible to infer the existence of this oxidation state from a study of the ESR absorption spectra. Although the divalent state of gold is one of the most interesting oxidation states in transition metal chemistry, only a few paramagnetic Au 2+ complexes have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Although the early publications by Bond et al [1,2] and Parravano et al [3,4] reported that small gold particles exhibited catalytic activity for some reactions, such as hydrogenation of olefins and oxygen transfer reactions, gold was generally considered to be catalytically inactive [5]. Over the past 20 years, the volume of literature on the application of gold catalysts has been steadily increasing since Haruta reported that highly dispersed gold particles supported on metal oxides are extremely active for CO oxidation [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Gates and coworkers reported that a supported mononuclear gold complex was active for ethylene hydrogenation at 353 K [11]. Recently, Iwasawa and coworkers [12][13][14][15][16] prepared highly active CO oxidation catalysts by grafting Au-phosphine complexes onto as-precipitated Ti(OH) 4 . They found that the as-precipitated Ti(OH) 4 was essential for obtaining highly dispersed gold catalysts and the use of a conventional TiO 2 support resulted in a much less active catalyst with a particle size greater than 15 nm.…”
Section: Introductionmentioning
confidence: 99%
“…The first one was aimed at reducing the magnitude of the void scattering through some experimental procedures (Gunn, 1958). This procedure, known as the pore-maskant method, has been used in some SAXS laboratories (White et al, 1972;Renouprez & Imelik, 1973;Renouprez et al, 1974;Cocco et al, 1979;Lopez et al, 1992), but it is limited by the fact that the imbibition liquids may affect the catalyst in unknown ways, and it is difficult to ensure reproducibility in filling the pores. The intensities due to the metal phase can be used to determine the average particle sizes and/or the particle-size distribution N(d) (d = characteristic dimension of the particle).…”
Section: Catalystsmentioning
confidence: 99%